Evaluating the applicability of a risk-based approach (decision tree) to mycotoxins mitigation - Hanlon, P.R.; Bandyopadhyay, Ranajit; Brorby, G.P. (2019)
Mycotoxins are secondary metabolites of naturally occurring fungi often associated with the production and storage of certain grains. Humans have thus been exposed throughout history to mycotoxins inherent in many foods consumed as part of standard diets. The primary aim of this work was to evaluate a hypothesis on whether a foundational framework (decision tree) previously developed by the North American Branch of the International Life Sciences Institute (ILSI North America) Food and Chemical Safety Committee for a risk-based approach to mitigation of process-formed compounds could be applied to other not-readily-avoidable substances, such as mycotoxins. It was concluded that the ILSI North America decision tree was generally applicable to mycotoxins, although with the recognition that specific steps and/or specific mycotoxins may require the development of additional criteria, especially within developing nations.